2020
DOI: 10.1109/access.2020.2972910
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Joint Power Allocation and Energy Cooperation for Hybrid-Powered Comp-Enabled HetNet

Abstract: Base station (BS) coordination with respect to data and energy cooperation has recently emerged as a potential solution for enhancing the energy efficiency (EE) of multi-cell multi-tier cellular network architecture. This work studies the EE maximization problem in a hybrid-powered (grid and renewable energy source) heterogeneous network (HetNet) where the data and energy are jointly coordinated among the BSs. We propose a combinatorial optimization algorithm to maximize the system EE with the aim to reduce gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…To the best of our knowledge, this is the first work to incorporate base station switching (BS-Sw) into a CoMP-enabled hybrid-powered BS connected to a smart grid. Unlike the work in [12], which proposes a joint power allocation and energy cooperation for a CoMP-enabled HetNet, this work extends the previous works further by considering the BS-Sw and power allocation in a CoMP-enabled HetNet, which employs smart grid for energy cooperation. The problem formulated is more challenging by taking BS-Sw into account because the strategy to switch off the BS has a direct impact on the power allocation and energy cooperation.…”
Section: Related Work and Contributionsmentioning
confidence: 98%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first work to incorporate base station switching (BS-Sw) into a CoMP-enabled hybrid-powered BS connected to a smart grid. Unlike the work in [12], which proposes a joint power allocation and energy cooperation for a CoMP-enabled HetNet, this work extends the previous works further by considering the BS-Sw and power allocation in a CoMP-enabled HetNet, which employs smart grid for energy cooperation. The problem formulated is more challenging by taking BS-Sw into account because the strategy to switch off the BS has a direct impact on the power allocation and energy cooperation.…”
Section: Related Work and Contributionsmentioning
confidence: 98%
“…To obtain the optimal transmit power, the PA problem can be converted into Lagrangian optimisation and the problem can be solved using the Lagrangian dual method. It is worth noting that this method was used in the author's previous work to solve a similar problem [12]. First, the Lagrangian function of the PA optimisation problem is formed as in Equation ( 5).…”
Section: Dual Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [16], the authors investigated CoMP JT in the multitier UDN and analyzed the performance of network energy efficiency. In [17], the system energy efficiency maximization problem in hybridpowered heterogeneous network (HetNet) is solved by joint optimization of data and energy among coordinated BSs. In [18], the authors focused on the CoMP JT in nonorthogonal multiple access (NOMA) and proposed a distributed power optimization approach which can obtain significant gains in energy efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…It should be pointed out that the power supply problem has been solved in regions where it is possible to extend the electrical grid in combination with renewable resources. In [37], the authors present a study on the maximization of energy efficiency within a heterogeneous network that includes various types of networks, in addition to renewable energy sources, and the information and energy data were coordinated synchronously between base stations. In addition, in [38], it was reported that a control system based on the management and administration of energy within a home can be programmed efficiently and can integrate an RES.…”
Section: Related Workmentioning
confidence: 99%